BIOMEDICAL RESEARCH IN THE MIDDLE EASTERN COUNTRIES: UPDATE AND INSIGHT USING SCIMAGO JOURNAL RANK INDICATOR - Alenzi, Faris QB; Lotfy, Mahmoud; Nasif, Wasam; Shahat, Mohamed El-; Abusini, Hasan; Alenazi, Mohamed; Alenazi, Fawwaz A; Tamimi, Waleed G; Salem, Mohamed L (Journal of Ayub Medical College Abbottabad, 2010)
Background: There is a dire need in the Arab world and Middle Eastern countries to reform the higher education, research policy and planning for improving the quality to meet the needs of modern society. The impact factor (IF) was developed in the 1960s by Eugene Garfield of the Institute for Scientific Information (ISI) in the USA. It has been extensively used for more than 40 years. The SCImago Journal Rank (SJR) indicator belongs to this new family of indicators based on eigenvector centrality was introduced since 2007. The SJR indicator is a size-independent metric aimed at measuring the current ’˜average prestige per paper’ of journals for use in research evaluation processes. Methods: We present the status of the biomedical scientific research in the Middle Eastern countries through the newly developed SJR indicator showing some of the proposed ways that clearly can be applied for enhancing and development of that field in the Middle Eastern countries. Results: During the period from 1996 to 2008, Northern America, Western Europe and Asiatic region are the major contributors of the scientific research Worldwide. In the Middle East, the prominent two main Arab countries are Egypt and Saudi Arabia, nevertheless, they need more planned strategies for optimal contribution to their Middle East, Arab region and the World, despite the tangible achievements of the Arab states in the higher education and scientific research during the last decade. Conclusion: The SJR is seemingly satisfactory for ranking the countries for their scientific contribution and impact. Keywords: Biomedical Research, Middle East, SJR